Living with a Foggy Future: Experiences of Caregivers of Hemodialysis Patients - Fatemeh Ghapanvari; Seyedehzahra Hosseinigolafshani (Kerman University of Medical Sciences, 2024)
Background: Caregivers of hemodialysis patients experience several daily challenges due to the specific condition of their patients. It is necessary to study the challenges of this group to reduce the adverse effects on the caregivers and the patients. Accordingly, the present study aimed to describe the caregivers' lived experiences of caring for hemodialysis patients.Methods: This was a qualitative study conducted using a phenomenological approach. The participants were 21 caregivers of hemodialysis patients from three hemodialysis centers in Qazvin, Iran who were selected using purposive and snowball sampling. Data were collected through in-depth semi-structured interviews and analyzed using Colaizzi's seven-step method.Results: A total of 107 primary codes, 15 subcategories, 7 categories, and 3 main themes were extracted from the analysis of the interviews. The main themes included caregiver as the central pillar, fear of the foggy future, and the heavy burden of being judged by others.Conclusion: Caring for patients with hemodialysis constantly imposes many challenges for caregivers. The managers of hospitals and hemodialysis clinics can prevent the severe consequences experienced by caregivers and patients by planning and implementing individual development training courses and effective policies to enable caregivers.